Effect of PEGDE addition on rheological and mechanical properties of bisphenol E cyanate ester. Issue 1 (19th March 2013) - Sheng, Xia; Hanus, Riley; Bauer, Amy; Kessler, Michael R.
Abstract Cyanate esters are a group of resins with exceptional thermal and mechanical properties and are often blended with lower cost epoxy resins. These blends are often brittle, and a toughening method, such as the addition of soft segments, is necessary. Poly(ethylene glycol) diglycidyl ether, or PEGDE, was added to bisphenol E cyanate ester as a toughening agent. PEGDE was added at loadings of 0–30 wt %, and rheological and mechanical properties were analyzed after curing. As PEGDE loading was increased, the gel point increased accordingly while the activation energy of gelation decreased, indicating PEGDE accelerated the gelation process. Dynamic mechanical analysis results indicated a decrease in glass transition temperature as the PEGDE loading increased. Three‐point bending tests yielded similar toughness to the neat BECy at low PEGDE loadings, with a dramatic increase at loadings of 25 and 30 wt % PEGDE. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013